Spectral characteristics of Compton backscattering sources. Linear and nonlinear modes; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 355 : Channeling 2014: Charged & Neutral Particles Channeling Phenomena - Potylitsyn A. P. Alexander Petrovich (2015, 2015)
Title screen